2020
DOI: 10.3386/w27427
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and the Demand for Online Food Shopping Services: Empirical Evidence from Taiwan

Abstract: The authors thank Dong-Liaring Yang for sharing his management experience with the Ubox platform and for assistance with data collection. Valuable comments from Feng-An Yang and other seminar participants at National Taiwan University are also appreciated. The views expressed herein are those of the authors and should not be attributed to the Ubox Corporation. The authors are responsible for any remaining errors. The views expressed herein are those of the authors and do not necessarily reflect the views of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 10 publications
1
46
1
4
Order By: Relevance
“…Approximately 7% of the sample that was responsible for doing groceries indicated to that they ordered their groceries more frequently online than usual. This is slightly lower than the figure observed in Italy (9%) ( Di Renzo et al, 2020 ) but much lower than the online food ordering figures during the pandemic observed in Asia ( Chang & Meyerhoefer, 2020 ; Zhao et al, 2020 ). These increases in online food ordering may on the one hand related with the request to stay at home as much as possible (for which food delivery is extremely suitable) but it may also be related with fears for being infected in places like shops ( Gerhold, 2020 ).…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Approximately 7% of the sample that was responsible for doing groceries indicated to that they ordered their groceries more frequently online than usual. This is slightly lower than the figure observed in Italy (9%) ( Di Renzo et al, 2020 ) but much lower than the online food ordering figures during the pandemic observed in Asia ( Chang & Meyerhoefer, 2020 ; Zhao et al, 2020 ). These increases in online food ordering may on the one hand related with the request to stay at home as much as possible (for which food delivery is extremely suitable) but it may also be related with fears for being infected in places like shops ( Gerhold, 2020 ).…”
Section: Discussioncontrasting
confidence: 65%
“…80.1% of fruits and 77.2% of vegetables) via in-person grocery shopping ( Zhao et al, 2020 ) and it was observed that online food shopping increased in Taiwan; every additional confirmed case of COVID-19 increased online sales by 5.7% and the number of customers by 4.9%. ( Chang & Meyerhoefer, 2020 ). Italian insights indicated that the minority of participants used online delivery during lockdown (9%) although it was not observed how this changed compared to pre-lockdown ( Di Renzo et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the nationwide lockdown, many individuals were forced to stay inside their homes and they preferred to buy food items through OFDs. Local governments also encouraged individuals to buy products online in order to reduce the spread of the disease (Chang & Meyerhoefer, 2020;Richards & Rickard, 2020; The Times of India, 2020b) and this discussion clears the positive effects of the perceived benefits of OFDs. OFDs are more convenient, safe and cost-effective for individuals than going to hotels and restaurants.…”
Section: Perceived Benefitsmentioning
confidence: 99%
“…An increasing number of studies have examined the unprecedented growth of e-commerce with the spread of COVID-19 (Donthu and Gustafsson, 2020). In particular, a rapid increase in online food trade has been reported worldwide, including in China (Gao et al, 2020), Taiwan (Chang and Meyerhoefer, 2020), and Germany (Dannenberg et al, 2020). Because food purchasing is a critical everyday activity, if online shopping habits to obtain food become established, future going-out activities may be suppressed even after the pandemic ends.…”
Section: Introductionmentioning
confidence: 99%